М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
exomashka
exomashka
06.02.2020 01:47 •  Алгебра

Найди значение выражение
1)2⁶; 2)(-7)²; 3)(0,6)²; 4)7²; 5)(½)³;
6)(-½)²; 7)(1⅕)³; 8)(-1½)⁴​

👇
Ответ:
OMGKristallikOMG
OMGKristallikOMG
06.02.2020

Объяснение:

2^{6} = 64

(-7)^2 = 49

(0.6)^2 = 0.36

7^2 = 49

(1/2)^3 = 1/8

(-1/2)^2 = 1/4

(1\frac{1}{5})^3 = (1.2) ^ 3 = 1,728

(-1½)⁴ = (3/2)^4 = 81/8

4,8(4 оценок)
Открыть все ответы
Ответ:

Объяснение:

Система уравнений:

x/2 +y/2 -2xy=16          |×2

x+y=-2

x+y-4xy=32

-2-4xy=32

-4xy=32+2

-4xy=34                    |2

x=-17/(2y)

-17/(2y) +y=-2

(-17+2y²)/(2y)=-2

-17+2y²=-4y

2y²+4y-17=0; D=16+136=152

y₁=(-4-2√38)4=(-2-√38)/2

y₂=(-4+2√38)4=(√38 -2)/2

x₁+(-2-√38)/2=-2; x₁=(-4+2+√38)/2=(√38 -2)/2

x₂+(√38 -2)/2=-2; x₂=(-4-√38 +2)/2=(-2-√38)/2

ответ: ((√38 -2)/2; (-2-√38)/2); ((-2-√38)/2; (√38 -2)/2).

Система уравнений:

x/2 +y/2 +2xy=4

x-y=4

x/2 +y/2 +2xy=x-y                  |×2

x+y+4xy=2x-2y

4xy=2x-2y-x-y

4xy=x-3y

x-4xy=3y

x(1-4y)=3y

x=(3y)/(1-4y)

(3y)/(1-4y) -y=4

(3y-y+4y²)/(1-4y)=4

2(y+2y²)=4(1-4y)                   |2

2y²+y-2+8y=0

2y²+9y-2=0; D=81+16=97

y₁=(-9-√97)/4

y₂=(-9+√97)/4=(√97 -9)/4

x₁ -(-9-√97)/4=4; x₁=(16-9-√97)/4=(7-√97)/4

x₂ -(√97 -9)/4=4; x₂=(16+√97 -9)/4=(7+√97)/4

ответ: ((7-√97)/4; (-9-√97)/4); ((7+√97)/4; (√97 -9)/4).

4,6(69 оценок)
Ответ:
rimmabuketova
rimmabuketova
06.02.2020
1) 0,5(2y-1) - (0.5-0.2y)+1=0
1y-0.5-0.5+0.2y+1=0
1.2y=0
y=0
ответ: 0

2) (x² +3x+2)(x² +3x+4)=8
(x² +3x+2)(x² +3x+2+2)=8

y=x² +3x+2
y(y+2)=8
y² +2y-8=0
D=4+32=36
y₁=(-2-6)/2= -4
y₂=(-2+6)/2=2

При у= -4
x² +3x+2= -4
x² +3x+2+4=0
x² +3x+6=0
D=9-24<0
нет решений.

При у=2
x² +3x+2=2
x² +3x+2-2=0
x² +3x=0
x(x+3)=0
x=0       x+3=0
             x= -3
ответ: -3;  0.

3) (x² -2x-3)(4-x² +2x)= -2
(x² -2x-3)*(-(x² -2x-4))= -2
(x² -2x-3)(x² -2x-3-1)=2

y=x² -2x-3
y(y-1)=2
y² -y-2=0
D=1+8=9
y₁=(1-3)/2= -1
y₂=(1+3)/2=2

При у= -1
x² -2x-3= -1
x² -2x-3+1=0
x² -2x-2=0
D=4+8=12
x₁=(2-√12)/2=(2-2√3)/2=1-√3
x₂=1+√3
ответ: 1-√3;  1+√3

4) (x² -x-11)(x² -x-21)= -9
(x² -x-11)(x² -x-11-10)= -9

y=x² -x-11
y(y-10)= -9
y² -10y+9=0
D=100-36=64
y₁=(10-8)/2=1
y₂=(10+8)/2=9

При у=1
x² -x-11=1
x² -x-11-1=0
x² -x-12=0
D=1+48=49
x₁=(1-7)/2= -3
x₂=(1+7)/2=4

При у=9
x² -x-11=9
x² -x-11-9=0
x² -x-20=0
D=1+80=81
x₁=(1-9)/2= -4
x₂=(1+9)/2=5

ответ: -4; -3; 4; 5.
4,8(48 оценок)
Новые ответы от MOGZ: Алгебра
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ